ANALISIS PEMANFAATAN POJOK BACA DALAM MENINGKATKAN LITERASI MEMBACA SISWA KELAS V SD NEGERI 105288 SEI ROTAN - Rahmadita, Alifia; Luthfiani, Rini; Br. Saragih, Rayna; Rahma, Mahfira; Hutagalung, Trisnawati; Syafiq, Raifan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Since it will help them learn and comprehend information, reading literacy is seen to be a crucial skill for primary school pupils to develop. Unfortunately, due to a lack of motivation and reading resources, pupils' interest in and literacy in reading remain very low. The purpose of this study was to look at how reading nooks may help fifth-grade students at SD Negeri 105288 Sei Rotan become more literate readers. The mixed method design was used in this investigation. A class instructor and twenty-six fifth-graders are the study's subjects. Questionnaires, observations, interviews, and documentation were used to collect data. While qualitative data were studied descriptively, quantitative data were assessed using percentages. The analysis revealed that the mean score for questionnaires was 78.14%, categorized as good. It was found out from the interviewees that reading corners helped in raising students’ reading interest, making them use their spare time for reading, in improving reading fluency skills among younger grade level pupils, and in enhancing reading comprehension skills among senior grade levels pupils. The use of reading corners became more evident because of the school’s literacy program, which includes a reading exercise before each lesson lasts for about 15 minutes and the regular discussion of books. However, the adoption of reading corners has its own difficulties, specifically, the lack of available books.